Vesico-amniotic shunt insertion prior to the completion of 16 weeks results in improved preservation of renal function in surviving fetuses with isolated severe lower urinary tract obstruction (LUTO) - Kohl, Thomas; Fimmers, Rolf; Axt-Fliedner, Roland; Degenhardt, Jan; Brückmann, Moritz (Journal of pediatric urology, 2022)
Purpose - The purpose of this retrospective cohort study was to compare the outcome of human fetuses with isolated severe lower urinary tract obstructions (LUTO) that were first treated before the completion of 16 weeks of gestation to fetuses first treated later in gestation. - Patients and methods - Vesicoamniotic shunt insertion (VAS) was performed in 63 subsequent fetuses with LUTO between 12 + 5 and 30 + 3 weeks. The fetuses were analyzed in three groups: Group-I-fetuses underwent their first intervention until the completion of 16 weeks, Group-II-fetuses were first treated between 16 + 1 and 24 + 0 weeks and Group-III-fetuses beyond 24 + 1 weeks. Renal and pulmonary outcome parameters and complicating factors were assessed. - Results - - All mothers tolerated the procedures well. Overall fetal survival was 47 of 63 (75%). The mean age at delivery of survivors was 35 weeks. 68% of Group-I-fetuses, 77% of group-II-fetuses, and 100% of group-III-fetuses survived beyond postnatal hospital discharge. Amongst the survivors the chance for normal renal function was higher for group I with 79% (15/19) compared to first fetal intervention after the completion of 16 weeks with 32% (9/28, p = 0.003, OR = 7.9 [2.0, 30.8] 95% CI). Clinically relevant pulmonary hypoplasia was observed in 11% of Group-I-, 27% of Group-II-, and 20% of Group-III-fetuses. - Conclusions - Early intervention in fetal LUTO before the completion of 16 weeks may achieve a higher rate of normal renal and pulmonary function in survivors than treatment beyond that point in time. This observation is important for the future management of this challenging patient population.Summary FigureImage 1
Online verfügbar: 19. Januar 2022, Artikelversion: 26. Mai 2022
Gesehen am 18.03.2024